From four to zero? The social mechanisms of symbolic domination in the UK accounting field. (March 2015) - Stringfellow, Lindsay; McMeeking, Kevin; Maclean, Mairi
Abstract: Corporate failures and financial crises periodically lead to speculation and critique of the Big Four in the UK. Wide-reaching regulatory changes and reforms have emerged as a consequence, yet the overall dominance of the large accounting firms remains an immutable truth. This paper explores the dominance of the Big Four drawing on Bourdieu's rich system of thought, and in particular the role of symbolic productions, and how symbolic power and symbolic violence are deployed to secure the social integration of an arbitrary order. We document the social mechanisms of symbolic domination that secure the Big Four's position in the social structure of professional accounting firms. We identify a circular system of double-structured domination, where three mechanisms of euphemised discourse, rites of institution and socialisation normalise symbolic systems and disabling constraints for smaller firms. In addition to interviewing informants working in the field, this paper examines recent political challenges that have placed the role of the Big Four and their domination under increasing scrutiny. These challenges bring into focus issues of recognition and resistance to symbolic modes of domination, and we contemplate the impact of such discourses on the dynamics of the UK accounting field, and the Big Four's continued influence.